2021
DOI: 10.3390/app112211031
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Nanodelivery Perspectives for Treatment of Cardiovascular Diseases

Abstract: Bioactive compounds are comprised of small quantities of extra nutritional constituents providing both health benefits and enhanced nutritional value, based on their ability to modulate one or more metabolic processes. Plant-based diets are being thoroughly researched for their cardiovascular properties and effectiveness against cancer. Flavonoids, phytoestrogens, phenolic compounds, and carotenoids are some of the bioactive compounds that aim to work in prevention and treating the cardiovascular disease in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 171 publications
0
6
0
Order By: Relevance
“…Many studies have found that dietary therapies can significantly lower cardiovascular risk ( Cavalu et al, 2013 ; Sindhu et al., 2021 ). A Mediterranean diet has been found to reduce the prevalence of CVDs as well as mortality rates.…”
Section: Interventionsmentioning
confidence: 99%
“…Many studies have found that dietary therapies can significantly lower cardiovascular risk ( Cavalu et al, 2013 ; Sindhu et al., 2021 ). A Mediterranean diet has been found to reduce the prevalence of CVDs as well as mortality rates.…”
Section: Interventionsmentioning
confidence: 99%
“…The development of nano delivery systems has been a successful way to overcome the pharmacokinetic limitations of many natural compounds, allowing them to broaden their medicinal application [18]. Sindhu et al [19] present in this Special Issue a review of the literature on the development of nano formulations involving natural compounds with application in the treatment of cardiovascular diseases, highlighting those with the most significant results for the prevention and treatment of this type of disease, that is, cases involved in clinical studies.…”
Section: Contributionsmentioning
confidence: 99%
“…The recent developments in nanotechnology have helped in the preparation of the nanoformulation of drugs with the sustained release of bioactive molecules for longer periods. Accordingly, the nanosuspension formulation enhances the bioavailability of poorly soluble phytoconstituents with controlled delivery, thus improving their bioactivity profiles [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%